Awareness of Zoonotic Diseases among Dog Owners in an Urban Area of Kancheepuram District, Tamilnadu - Sushmitha Saran; Gopalakrishnan; Ananthaeashwar VM (Medsci Publications, 2021)
Background: Dogs are the most companion animals of humans and hence they are the direct or indirect source of zoonotic infections. Rabies is an important zoonotic disease in which dogs are the principle reservoir. Only if the dog owners are well informed and aware of the various zoonotic diseases, they will be able to take preventive measures to tackle the same. AIM: This study was done with the aim to assess the awareness of zoonotic diseases among dog owners. MATERIAL & METHODS: This is a community- based cross sectional study, conducted at Kanchipuram district, Tamil Nadu with a convenient sample of 150 adults. A semi structured questionnaire was used to collect the data and was analysed using SPSS 20 version. RESULTS: Among the study participants, most of the respondents were in the age group between 18 to 40 years. Around 64.7% of the participants were females and 35.3% were males. Among the zoonotic diseases, 94% were aware of rabies. About 92 % were aware that deworming is good for their pet and 92% were aware that vaccines could prevent zoonotic diseases. Around 53.3% had the source of information from family and friends and 60.7% had from veterinary doctors. Conclusion: The study found knowledge gaps about zoonotic disease caused due to fleas and ticks. Regular deworming was not done by many dog owners. Veterinarians play an important role in pet owners education regarding zoonotic disease.